Rhizosphere pH and cation‐anion balance determine the exudation of nitrification inhibitor 3‐epi‐brachialactone suggesting release via secondary transport - Egenolf, Konrad; Verma, Supriya; Schöne, Jochen; Klaiber, Iris; Arango, Jacobo; Cadisch, Georg; Neumann, Günter; Rasche, Frank (Wiley, 2021)
Biological nitrification inhibition (BNI) of Brachiaria humidicola has been attributed to nitrification-inhibiting fusicoccanes, most prominently 3-epi-brachialactone. However, its release mechanism from B. humidicola roots remains elusive. Two hydroponic experiments were performed to investigate the role of rhizosphere pH and nutritional N form in regulating 3-epi-brachialactone release by B. humidicola and verify the underlying release pathway. Low rhizosphere pH and NH4 + nutrition promoted 3-epi-brachialactone exudation. However, the substitution of NH4 + by K+ revealed that the NH4 + effect was not founded in a direct physiological response to the N form but was related to the cation-anion balance during nutrient uptake. Release of 3-epi-brachialactone correlated with the transmembrane proton gradient ΔpH and NH4 + uptake (R2 = 0.92 for high ~6.8 and R2 = 0.84 for low ~4.2 trap solution pH). This corroborated the release of 3-epi-brachialactone through secondary transport, with the proton motive force (ΔP) defining transport rates across the plasma membrane. It was concluded that 3-epi-brachialactone release cannot be conceptualized as a regulated response to soil pH or NH4 + availability, but merely as the result of associated changes in ΔP.